Assessing the role of qualitative factors in pandemic responses. (28th November 2021) - Tan, Melisa Mei Jin; Neill, Rachel; Haldane, Victoria; Jung, Anne-Sophie; De Foo, Chuan; Tan, See Mieng; Shrestha, Pami; Verma, Monica; Bonk, Mathias; Abdalla, Salma M; Legido-Quigley, Helena
Abstract : Melisa Tan and colleagues argue that assessments of national pandemic preparedness and response capacities should be extended to include social factors, leadership, and use of evidence